Molecular Dynamic Simulation of Zigzag Silicon Carbide Nanoribbon - Nguyen, Hang Thi Thuy (Communications in Physics, 2021)
The heating process of zigzag silicon carbide nanoribbon (SiCNR) is studied via molecular dynamics (MD) simulation. The initial model contained 10000 atoms is heating from 50K to 6000K to study the structural evolution of zigzag SiCNR. The melting point is defined at 4010K, the phase transition from solid to liquid exhibits the first-order type. The mechanism of structural evolution upon heating is studied based on the radiral distribution functions, coordination number, ring distributions, and angle distributions